CITIZENSHIP AND INDIGENOUS CHALLENGES IN NIGERIA: DRAWING INSIGHTS FROM BEST PRACTICES IN THE UNITED STATES - AUWALU MUSA (International Studies Journal)
This paper delves into the intricacies of Nigerian citizenship, particularly the indigene-settler dilemma, by drawing parallels with the U.S. citizenship model. The study utilizes secondary data and content analysis to explore the complex interplay of belonging, rights, and identity in American citizenship, highlighting the role of birthright citizenship as stipulated by the 14th Amendment. This U.S. principle, prioritizing birthplace over lineage, contrasts with the descent-based approaches prevalent in Nigeria and some other countries. The analysis reveals that the U.S. model, by automatically conferring citizenship to those born on its soil regardless of parental heritage, fosters inclusivity and national integration. This paper suggests that Nigeria could benefit from a more inclusive citizenship model that combines elements of birthplace and lineage. By adopting lessons from the U.S., including the emphasis on inclusivity and rights-based citizenship, Nigeria could address its indigene-settler conflicts more effectively. This study makes a significant contribution to the literature by providing a comparative analysis of citizenship models, highlighting the potential benefits of the U.S. approach for Nigeria. Unlike previous studies that may focus solely on Nigerian citizenship issues or U.S. citizenship in isolation, this research uniquely bridges the two contexts to offer a fresh perspective on how Nigeria might reform its citizenship policies. The recommendations propose a nuanced approach to citizenship in Nigeria, aiming for policies that support national unity and integration, drawing on the U.S. experience as a potential guide for reform. By examining the successful elements of the U.S. model, this paper provides a roadmap for Nigeria to enhance its citizenship framework, promoting greater inclusivity and social cohesion.